ANTIRADICAL AND HEPATOPROTECTIVE PROPERTIES OF PARMELIA VAGANS L. - Tugel Sarsenbayev; Bekaidar Bakirov; Aikhanim Bauyrzhanova; Merey Meirbek; Yryskeldi Abdramanov; Kimanova Sharapat; Ibatayev Zharkyn; Madina Tleugabyl; Bilyalova Anel (Theoretical Hypotheses and Empirical Results, 2025)
in vitro and in vivo investigation the antiradical and hepatoprotective activity of the Parmelia vagans L. ethanol extract from the Kazakhstan